2016
DOI: 10.3324/haematol.2016.144576
|View full text |Cite
|
Sign up to set email alerts
|

Real-world results of ibrutinib in patients with relapsed or refractory chronic lymphocytic leukemia: data from 95 consecutive patients treated in a compassionate use program. A study from the Swedish Chronic Lymphocytic Leukemia Group

Abstract: Ibrutinib, a Bruton's tyrosine kinase inhibitor is approved for relapsed/refractory and del(17p)/TP53 mutated chronic lymphocytic leukemia. Discrepancies between clinical trials and routine healthcare are commonly observed in oncology. Herein we report real-world results for 95 poor prognosis Swedish patients treated with ibrutinib in a compassionate use program. Ninety-five consecutive patients (93 chronic lymphocytic leukemia, 2 small lymphocytic leukemia) were included in the study between May 2014 and May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
99
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 23 publications
17
99
7
2
Order By: Relevance
“…Long‐term results from this study (median follow‐up, 47 months) showed a median PFS of 32 months for this high‐risk patient subgroup (Jain et al , 2016). In a real‐world study of ibrutinib‐treated patients enrolled in a compassionate‐use programme, the estimated 10‐month PFS and OS rates were 71% and 78%, respectively, for 50 patients with del(17p) (Winqvist et al , 2016). In a real‐world study of ibrutinib‐treated patients in a named patient scheme, the estimated 12‐month discontinuation‐free progression and OS rates were 71% and 84%, respectively for 90 patients with del(17p) (UK CLL Forum 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long‐term results from this study (median follow‐up, 47 months) showed a median PFS of 32 months for this high‐risk patient subgroup (Jain et al , 2016). In a real‐world study of ibrutinib‐treated patients enrolled in a compassionate‐use programme, the estimated 10‐month PFS and OS rates were 71% and 78%, respectively, for 50 patients with del(17p) (Winqvist et al , 2016). In a real‐world study of ibrutinib‐treated patients in a named patient scheme, the estimated 12‐month discontinuation‐free progression and OS rates were 71% and 84%, respectively for 90 patients with del(17p) (UK CLL Forum 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although ibrutinib undoubtedly represents a significant advance in the treatment of patients with CLL and del(17p), it nevertheless appears that many R/R patients with del(17p) will ultimately relapse with ibrutinib therapy (Byrd et al , 2015; Winqvist et al , 2016). There may be a plateau in the rate of RT in patients, suggesting that the risk of developing RT is biologically determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the multi-center Swedish experience presented data on 95 CLL patients treated for a median of 10.2 months, with a 10 month PFS of 77% and OS of 83%. 9 There are a number of potential reasons why the rates of ibrutinib discontinuation and survival are likely to be worse in a real-world setting than in a clinical trial. Patients treated outside of a clinical trial are more likely to have poorer performance status and more comorbidities.…”
Section: © Ferrata Storti Foundationmentioning
confidence: 99%
“…Despite an excellent safety profile and high tolerability, a large number of patients have bleeding as a side effect. [1][2][3] These events are typically low grade, presenting as mucosal or skin bleeding; 1,3 however, more severe bleeding has been reported, and is a concern when scheduling surgery or if anti-coagulants are needed, such as in patients with atrial fibrillation.…”
mentioning
confidence: 99%